A Curriculum-Based Islamic Framework for Ihsān and Career Development - Issa Ndungo (Formad English Foundation NTB Jakarta, 2026)
Career development within many Muslim education systems is often treated as external to the curriculum, with emphasis placed on academic certification rather than formative educational processes. Such degree-centred approaches are increasingly inadequate in contemporary contexts marked by rapid socio-economic change and ethical uncertainty. This conceptual paper proposes a curriculum-based Islamic framework for career development grounded in the Qur’an and Sunnah, positioning ihsān (excellence) as the ethical core of educational formation. Drawing on Islamic epistemology and curriculum theory, the paper reframes career development as a gradual process embedded within curriculum aims rather than a post-school concern. It introduces the ISIT framework, Intention (niyyah), Skill (mahārah), Integrity (amānah), and Reliance upon Allah (tawakkul) to conceptualise how curriculum can cultivate ethically grounded, competent, and responsible learners. The paper further clarifies the complementary roles of learners, parents, communities, and divine reliance in sustaining ihsān within career development. It argues that ihsān flourishes when responsibility is properly aligned and weakens when effort, guidance, or reliance is misplaced. The framework contributes to Islamic education by offering a coherent, faith-consistent curriculum lens for understanding career development as an educational outcome.